Pendampingan Digitalisasi Dokumen Sekolah Dasar Berbasis Cloud menggunakan Google Workspace - Fathur Rizal; Muhammad Kholilul Hamdani; Moh. Maftuh; Moh. Rusdiyanto (Yayasan Literasi Altruis Khatulistiwa, 2025)
The dominance of manual administration systems and low digital literacy are structural barriers to document management at Maesan District Elementary Schools. This community service activity aims to transform school administrative governance through the use of Google Workspace for Education, involving 20 participants consisting of administrative staff, school operators, and administrative teachers who have a very low initial competency level (score of 18.3%). The implementation method uses a participatory approach based on Problem-Based Learning and hands-on practice supported by infrastructure from partner CV. Nafiatul Ummah. The intervention was carried out through training on Cloud Storage features, document collaboration, and data management. The evaluation results showed a significant increase in competency of 71.7 points, with the average final score of participants reaching 90%. Real indicators of success are seen in the formation of a structured digital archive ecosystem, including the digitization of student master data, daily attendance automation using Google Forms, and efficient financial reporting based on Google Sheets, which has been proven to reduce work time from days to minutes. This program recommends the institutionalization of digitalization SOPs and ongoing technical assistance to ensure the long-term independence and security of school data.